Usage of Polcam Device for Parameter Monitoring and Traffic Flow Modelling - Jan Ondrus; Lubomir Cernicky (Communications - Scientific letters of the University of Zilina, 2016)
This article deals with a proposal of using the Polcam PC2006 device for obtaining the traffic flow characteristics. This device is a first of a kind at the University of Zilina. The aim was to perform a practical measurement with a floating vehicle on a selected road section I/18 Zilina - Strecno - Vrutky, evaluate basic characteristics of a traffic flow with consequent modelling and use of software tools. Three measurements were performed in road traffic under different conditions. Individual calculations based on data obtained from practical measurements are processed at the end of the article. The results obtained from the measurement are used for traffic flow modelling in the programme Aimsun.